Vertical Zika Virus Transmission at the Maternal-Fetal Interface - Guzeloglu-Kayisli, Ozlem; Kayisli, Umit Ali; Schatz, Frederick; Lockwood, Charles Joseph (Frontiers in Virology, 2022)
Zika virus (ZIKV) is spread by mosquito bites or via sexual or vertical transmission. ZIKV-infected adults are generally asymptomatic, but can display mild symptoms including fever, joint pain, rash and conjunctivitis. However, during pregnancy, vertical ZIKV transmission can cause placental dysfunction and elicit severe fetal defects, including microcephaly, retinopathy, fetal growth restriction and/or stillbirth. Since no FDA-approved vaccine or anti-viral agents are currently available, ZIKV infection poses a global maternal-fetal health challenge. The maternal-fetal interface consists of maternal decidual and immune cells as well as fetal-derived trophoblasts. Compared to other cell types at the maternal-fetal interface, syncytiotrophoblasts, which form the outer layer of floating villi, are less-permissive to ZIKV, thereby preventing ZIKV transmission to the underlying cytotrophoblasts and/or other cells such as Hofbauer cells or fetal endothelium in the villi. However, anchoring villi are tightly attached to the decidua and their cytotrophoblastic cell columns are ZIKV-permissive, suggesting this location as the most likely site of ZIKV vertical transmission. Thus, at the maternal-fetal interface, maternal decidual cells likely serve as a reservoir of ZIKV persistence since they: 1) overexpress viral entry molecules compared to trophoblasts; 2) are highly permissive to ZIKV infection in a gestational age-dependent manner (more easily infected earlier in gestation); 3) augment ZIKV infection of weakly permissive primary cytotrophoblast cultures; and 4) display local maternal-immune tolerance, which prolongs ZIKV survival to facilitate fetal transmission. This review focuses on molecular mechanisms underlying ZIKV infection of cells at the human maternal-fetal interface, thus highlighting how decidual cells enhance propagation of ZIKV in extravillous cytotrophoblasts and why development of agents that eliminate ZIKV persistence in reproductive tissues before pregnancy is crucial to prevent perinatal ZIKV transmission.